DIGITAL MARKETING STRATEGY FOR EXPLORE MISTER ALADIN PRODUCTS TO ATTRACT PURCHASES AT MISTER ALADIN - Janu Dimas Permadi; Rahmat Ingkadijaya; Sri Mariati (LPSDI Bina Patria, 2025)
Digital developments in Indonesia currently also affect the tourism sector, with the growth of digitalization having an impact, increasing competitiveness in the Online Travel Agent (OTA) industry. The existence of this competitiveness makes competitors innovate to provide the best service in order to attract purchases. The purpose of this study is to analyze customer interest in purchasing Explore Mister Aladin products, on the current Mister Aladin Platform, analyze the current digital marketing strategy of Explore Mister Aladin products, and build and develop a digital marketing strategy for Explore Mister Aladin products through the right social media channels to increase purchases at Mister Aladin. The approach to this research is qualitative with descriptive and SWOT analysis methods. The results of the study show that customer interest is influenced by trust and promotion, the current strategy is to use social media but is not yet optimal, and the resulting strategy is an aggressive strategy by developing technology that makes it easier for customers and building cooperation with vendors and business partners. To strengthen competitiveness, Mister Aladin must intensify digital advertising, expand partnerships with Key Opinion Leaders (KOLs), and improve social listening strategies and data-based customer loyalty programs.